The effects of mandatory ingredient and nutrition labelling for wine consumers – A qualitative study - Evelyn Pabst; Gergely Szolnoki; Simone Mueller Loose (Wine Economics and Policy, 2019)
Purpose: The purpose of this study is to examine how wine consumers react to ingredient and nutrition labelling. It examines how important this information is to consumers, how it affects their attitudes to wine as a natural product and whether it influences consumer demand for wine. Methodology: A qualitative approach with focus group discussions and an observation of back label usage was utilised to assess consumers’ reactions to this new information. Bias from artificial attention to back label information was thereby reduced compared to that found in direct quantitative research. Three focus groups, consisting of twenty-one wine-involved participants, were run in three different cities in Germany in September 2017. Findings: Only one-third of consumers who looked at the back label detected new-to-them nutrition or ingredient information. Most consumers overestimated the caloric value of wine, and nutritional information was largely not perceived as useful. Consumers’ first reaction was to be insecure and confused about ingredient information. Ingredient lists negatively affected the degree to which consumers perceived wine as a natural product. Even though some consumers preferred wines with shorter ingredient lists, most would not exclude a wine when shopping because of labelling that gave nutritional values and ingredients. Practical implications: Nutrition labelling will likely not affect consumers’ wine choices, except when it competes for space with more meaningful back label information such as food pairings and sensory descriptions. There is a niche for wine producers to offer wine with short or no ingredient lists to concerned, high-involved wine consumers. Average or low-involved wine consumers are expected to be less concerned. The industry should inform consumers about typical production procedures before ingredient lists are introduced. Limitations: Although the observational qualitative study has high external validity, its results cannot be generalised due to the small non-representative sample involved. Thus, further validation is required. Keywords: Nutrition labelling, Nutritional value, Ingredient list, Focus groups, Consumer observation, Wine